2018
DOI: 10.4140/tcp.n.2018.321
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in Assisted Living and Impact on Clinical Outcomes

Abstract: Continued research is needed to explore the factors that influence polypharmacy. Identification of these factors will help guide deprescribing so that medication management does not harm older adults physically or cause unnecessary financial burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The FFC-AL-EIT is a dissemination and implementation study focused on helping assisted living settings integrate Function Focused Care into routine care (Resnick et al, in press). Function Focused Care is a philosophy of care in which older adults are encouraged to engage in physical activity at their highest level during all care interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFC-AL-EIT is a dissemination and implementation study focused on helping assisted living settings integrate Function Focused Care into routine care (Resnick et al, in press). Function Focused Care is a philosophy of care in which older adults are encouraged to engage in physical activity at their highest level during all care interactions.…”
Section: Methodsmentioning
confidence: 99%
“…This study used baseline data from the first cohort of a study titled Dissemination and Implementation of Function Focused Care for Assisted Living Using the Evidence Integration Triangle (FFC-AL-EIT). The FFC-AL-EIT is a dissemination and implementation study focused on helping assisted living settings integrate function-focused care into routine care (Resnick et al, in press). Function-focused care is a philosophy of care in which older adults are encouraged to engage in physical activity at their highest level during all care interactions.…”
Section: Methodsmentioning
confidence: 99%
“…Polypharmacy (PP) is defined as the co-prescribing of multiple medications or concurrent use of more than five drugs [1][2][3][4][5]. Studies have found a positive correlation between patients experiencing PP and higher age, lower levels of education, and female gender [1].…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy (PP) is defined as the co-prescribing of multiple medications or concurrent use of more than five drugs [1][2][3][4][5]. Studies have found a positive correlation between patients experiencing PP and higher age, lower levels of education, and female gender [1]. PP can increase the risk of falls in patients, adverse drug reactions (ADR) caused by drug interaction, medication non-compliance, hospitalization, and damage to physiological capacity [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation